Barriers to Physical and Mental Health: Understanding the intersecting needs of Cambodian and Latino residents in urban communities - D’Anna, LH (J Immigr Minor Health, 2018)
BACKGROUND: A community needs assessment was conducted to explore barriers and facilitators to good physical and mental health among Cambodian and Latino residents in an urban community in Southern California. METHODS: Thirty-six Cambodians and 29 Latinos completed the interviewer-facilitated survey administered door-to-door, and another 20 Cambodian and 18 Latino residents participated in focus groups. RESULTS: Crime, limited knowledge of positive health behaviors, lack of access to affordable healthcare, and lack of access to safe spaces for recreational activities were identified as threats to good health. Participant recommendations to support health in the community included increasing police presence to improve safety and reduce violence, and increasing opportunities/locations for physical exercise. DISCUSSION: While differences between Cambodian and Latino residents exist, the identified threats and suggested improvements were primarily associated with environmental factors, highlighting the need for systems level approaches that recognize the relationship between community context and health.